2020
DOI: 10.1016/j.orcp.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Obesity prolongs the hospital stay in patients affected by COVID-19, and may impact on SARS-COV-2 shedding

Abstract: Introduction: On the last three months the new SARS-COV-2 coronavirus has created a pandemic, rapidly spreading all around the world. The aim of the study is to investigate whether obesity impacts on COVID-19 morbidity. Methods: One hundred consecutive patients with COVID-19 pneumonia admitted in our Medical Unit were evaluated. Anthropometric parameters and past medical history were registered. Nasopharyngeal swab samples and biochemical analysis were obtained at admission and during hospital stay. Results: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 26 publications
4
93
0
8
Order By: Relevance
“…19 One study reported that BMI, age and CRP were all related to prolongation of length of hospital stay. 20 Factors responsible for prolonged length of stay (LOS) in which the median was 11 days (IQR, 5-15 days) showed the most important were lower neutrophil counts , higher partial thrombin time (PT) ,lower D-Dimer were associated with prolonged length of stay at hospital. 21 A novel strategy to manage patients is triage based on disease severity with management of mild patients in shelter homes.…”
Section: Discussionmentioning
confidence: 99%
“…19 One study reported that BMI, age and CRP were all related to prolongation of length of hospital stay. 20 Factors responsible for prolonged length of stay (LOS) in which the median was 11 days (IQR, 5-15 days) showed the most important were lower neutrophil counts , higher partial thrombin time (PT) ,lower D-Dimer were associated with prolonged length of stay at hospital. 21 A novel strategy to manage patients is triage based on disease severity with management of mild patients in shelter homes.…”
Section: Discussionmentioning
confidence: 99%
“…This could be another point to note regarding the duration of the quarantine in these patients. Subjects with obesity affected by COVID-19 require longer hospitalization, more intensive and longer oxygen treatment, and they may have longer SARS-CoV-2 shedding [75]. This is probably due to the ACE2 on the adipose tissue in obese patients and because mTOR is activated in the adipose tissue.…”
Section: How Obesity Can Be Related To Sars-cov-2 Disease Pathophysiomentioning
confidence: 99%
“…Obese patients have an increased risk of COVID-19 critical illness leading to ICU admission or death compared to normal weight individuals ( Hajifathalian et al, 2020 ; Onder et al, 2020 ). The complications of obesity are complex, and a number of other factors may affect COVID-19 severity ( Edler et al, 2020 ; Englmeier, 2020 ; Korakas et al, 2020 ; Moriconi et al, 2020 ; Pinheiro et al, 2020 ). More than 500 million individuals are obese (body mass index ≥ 30 kg/m 2 ) globally, and thus understanding the mechanisms by which excess adiposity drives greater infection severity is critical for solving this global public health threat ( World Health Organization, 2020 ).…”
Section: Introductionmentioning
confidence: 99%